Synthesis, structural characterization, and photoluminescence properties of TTB-type PbTa2O6:Eu3+ phosphor - (:unkn) unknown (WILEY, 2017)
Undoped and Eu3+-doped tetragonaltungsten bronze (TTB) PbTa2O6 phosphors were synthesized by using solid-state reaction method. Synthesized samples were characterized by XRD, SEM-EDS, and photoluminescence analyses. XRD results revealed TTB-type crystal structure with single phase up to 10mol% Eu3+ doping concentration. In SEM-EDS analyses, elemental composition of Pb decreased with the increasing concentration of Eu3+. Emissions at the excitation wavelength of 398.5nm were observed at 593.2 and 618.8nm due to (D0F1)-D-5-F-7 transitions and (D0F2)-D-5-F-7 transitions, respectively. Emission increased with the increasing Eu3+ doping concentration up to 10mol% and not observed concentration quenching.
Keywords: luminescence; scanning electron microscopy; tantalum; tantalum compounds; X-ray methods; CRYSTAL-CHEMISTRY; EU3+ IONS; SYSTEM; BRONZE